Staphylococcal scalded skin syndrome in a very low birth weight preterm infant - S, Saleenas; Nair, PMC; James, Jemila; N, Anand (Indian Journal of Child Health, 2018)
Staphylococcal scalded skin syndrome (SSSS) is an exfoliative dermatitis produced by the toxins of some strains of staphylococci, predominantly phage Group 2, strains 71 and 55. It has been reported mostly in children under 5 years of age with few cases only reported in very preterm infants. The disease can be life threatening in very low birth weight preterm babies. We are reporting one such case to emphasize the importance for clinicians to not only recognize the clinical manifestations of SSSS but also the need to closely monitor infants, especially VLBW infants with SSSS for bacterial sepsis and other complications.